Estudo de caso: implantação de autenticação de usuários em redes sem fio empresarial utilizado o protocolo 802.1X - Maieski, Silas (2018)
This work conclusion of specialization course presents the implementation of the 802.1X protocol in business environment, aiming to expose the improvements presented by it in the authentication of users. Deployment was done using the IEEE 802.1X standard, authentication RADIUS protocol, CHAP authentication method, and Active Directory database. In order to minimize the risks of unauthorized access, the WPA2 method and AES algorithm were used. Upon completion of the installation, it is possible to observe the ease of creating new wireless networks, as well as better management and access permission. Access permission control is now only performed by the company's IT staff. It also ensured better performance in using the wireless network, limiting access only to authorized personnel. This protocol assisted in the control of user access and monitoring of users, benefiting the company.